FTAs and Philippine business: Evidence from transport, food, and electronics firms - Ganeshan Wignaraja; Dorothea Lazaro; Genevieve DeGuzman (Asian Development Bank Institute (ADBI), 2010)
Within East Asia, the outward-oriented Philippine economy is a latecomer to using free trade agreements (FTAs) as a trade policy instrument and has relied heavily on the Association of Southeast Asian Nations (ASEAN) for regional liberalization. While negotiating FTAs has consumed scarce time and other resources, limited attention has been hitherto given to evaluating the impact of FTAs - particularly the 15-year-old ASEAN Free Trade Area (AFTA) agreement - on business activity in the Philippines. Using a survey of 155 manufactured goods exporters from three sectors (transport equipment, processed foods, and electronics), this study deals with three questions: (i) Do firms use AFTA and why?; (ii) What impedes firms from using AFTA and other FTAs?; and (iii) What can be done to improve FTA use at firm level in the future? The study finds that utilization of AFTA is higher than expected from existing studies and is set to double in the future. Econometric analysis suggests that firm age, domestic ownership, awareness of FTAs, and membership in the transport sector increase the probability of using AFTA. Surprisingly, among nonusers, a lack of information is the biggest barrier to FTA use. Other impediments to use include the availability of export processing zone incentive schemes, low most-favored-nation rates (particularly in electronics), delays in origin administration, rent-seeking behavior, and nontariff measures in partner country markets. Interestingly, the majority of firms do not think that multiple rules of origin in overlapping Asian FTAs add significantly to business costs. However, there is room for improvement in the system of AFTA rules of origin (e.g., lower value content and introduction of self-certification mechanisms). The examination of institutional support reveals an excess demand for a range of support services (e.g., information, technology-based, and small or medium enterprise extension services) that will enable firms to use FTAs more effectively in the future. The paper concludes by making the case for better mainstreaming of FTAs into Philippine national trade policy and for improving support services to firms.
Keywords: F1; F15; O24; 330; Freihandelszone; Handelsregionalismus; ASEAN-Staaten; Außenhandelseffekt; Nahrungsmittelgewerbe; Elektronikindustrie; Philippinen